Strategi Manajemen Organisasi Pendidikan Islam dalam Menghadapi Tantangan Global - Muh Ibnu Sholeh (Fakultas Tarbiyah Institut Pesantren Sunan Drajat Lamongan, 2023)
The globalization of education has brought about significant changes in education systems around the world, technological developments, challenges of multiculturalism, and global competition are some of the main issues faced by Islamic education organizations in facing the globalization of education. Therefore, the management of Islamic education organizations must be able to overcome these challenges and maintain the high quality of Islamic education. This study uses library research methods (library research). Researchers study the literature, writings and sources that have a close relationship with the problem under study. Data collection by searching for sources from various sources such as books, journals, and existing research. The data obtained from the literature study were analyzed using an interactive qualitative model. This data analysis model consists of data collection, data reduction, data presentation, and drawing conclusions. management of Islamic education organizations to maintain the quality of education that is of high quality and relevant in facing the challenges of educational globalization.